Comparação dos efeitos tegumentares do tratamento da classe II com elásticos intermaxilares sem extração e com extração de dois pré-molares superiores - Tóttoli Segundo, Honório (2017)
The aim of this study was to compare the soft tissue changes of the treatment of Class II malocclusion with intermaxillary elastics without extraction and extraction of two upper premolars. For this purpose, a retrospective sample was selected with 41 individuals who presented at the beginning of the treatment a molar relation of at least bilateral 1/2 Class II. These individuals were divided into two groups: Group 1 consisted of 21 patients (11 females and 10 males), with initial mean age of 18.97 years (SD=11.12), treated for an average period of 3.15 years without extraction and only with intermaxillary elastics for the correction of Class II; Group 2: 20 patients (16 females and 4 males), with mean age of 17.40 years (SD=7.32), treated with extractions of two upper premolars and intermaxillary elastics for the correction of Class II malocclusion, in a mean period of 3.07 years. The soft tissue variables were measured using the software Dolphin Imaging Premium 11.7 on the cephalograms obtained before and at the end of the orthodontic treatment. For the comparison between the two groups regarding the distribution of the gender and severity of malocclusion, the chi-square test was used. To compare the quantitative measures between the two groups, the t-test was used. In all tests, a significance level of 5% (p <0.05) was adopted. The results showed significant difference in Li-Line E and N’-Sn-Pog’. The Class II correction without extractions and with intermaxillary elastics reduce facial convexity and two upper premolars extractions protocol results in lower lip protrusion. Both treatments improve equivalent effects on facial profile, except for lower lip retrusion with extraction protocol and facial convexity reduction in protocol without extractions